2013
DOI: 10.1179/1743676113y.0000000128
|View full text |Cite
|
Sign up to set email alerts
|

Study of CuO–SnO2heterojunction nanostructures for enhanced CO gas sensing properties

Abstract: In this study, a facile hydrothermal method was adopted to fabricate SnO 2 and CuO-SnO 2 nanoparticles. The CuO content was chosen as 5 mol.-% (sample 1), 10 mol.-% (sample 2) and 15 mol.-% (sample 3). Microstructures and surface morphologies for all samples were characterised by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM) and high resolution transmission electron microscopy (HRTEM). A systematic comparison study reveals an enhanced gas s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…The sensor exhibited response to ppb-level ethanol and response time was 1 s. In another study, gas sensors fabricated from SnO2-SnO nanocomposite with p-n heterojunctions exhibited an enhanced sensing performance for NO2 gas detection, with limit of detection and sensitivity of 0.1 ppm and 0.26 ppm −1 , respectively [518]. Another p-n heterojunction was demonstrated with CuO-SnO2 gas sensors for CO gas [519]. A sensor based on a hierarchical CoO/SnO2 heterojunction demonstrated response up to 145 when exposed to 100 ppm ethanol gas.…”
Section: Tin Oxidementioning
confidence: 99%
“…The sensor exhibited response to ppb-level ethanol and response time was 1 s. In another study, gas sensors fabricated from SnO2-SnO nanocomposite with p-n heterojunctions exhibited an enhanced sensing performance for NO2 gas detection, with limit of detection and sensitivity of 0.1 ppm and 0.26 ppm −1 , respectively [518]. Another p-n heterojunction was demonstrated with CuO-SnO2 gas sensors for CO gas [519]. A sensor based on a hierarchical CoO/SnO2 heterojunction demonstrated response up to 145 when exposed to 100 ppm ethanol gas.…”
Section: Tin Oxidementioning
confidence: 99%
“…When the SnO 2 surface is exposed to a reductive gas (H 2 S), the reductive gas (H 2 S) upon reacting with the oxygen species (O 2 − , O − , and O 2− ) reduces the concentration of the oxygen species on this surface, thereby increasing the electron concentration [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Oxygen species with different forms (O 2 − , O − and O 2− ), which are adsorbed on the SnO 2 surface, are reliant on sensing temperature; therefore, controlling the temperature of H 2 S sensor is vital.…”
Section: Introductionmentioning
confidence: 99%
“…The study has shown that the composite powders could exhibit higher photocatalytic activity compared to standard Degussa P25 TiO 2 nanoparticles. Due to this success, CuO–SnO 2 heterostructures were then produced by others using different methods such as electrospinning, spray pyrolysis, combustion synthesis, solution casting, doctor blade, and hydrothermal synthesis in thin film, fiber and powder forms to reveal their potential in gas sensing, H 2 production, dye degradation, and Li‐ion battery applications . Recently, Wang et al, prepared SnO 2 ‐CuO hollow fibers in the presence of camphene as the morphology controlling agent.…”
Section: Introductionmentioning
confidence: 99%